A Comprehensive Approach to Nearly Zero Energy Buildings and Districts: Analysis of a Region Undergoing Energy Transition - Georgios Martinopoulos; Alexandros Tsimpoukis; Vasileios Sougkakis; Petros Dallas; Komninos Angelakoglou; Paraskevi Giourka; Nikolaos Nikolopoulos (Energies, 2024)
This paper explores the development of positive energy communities using Eordaia, Greece, as a case study. The approach combines building and district-level energy analysis to achieve nearly zero energy performance through retrofitting, district-level storage systems, and renewable energy technologies. A parametric analysis utilizing RETSCREEN Expert and EnergyPlan software determines the optimal mix of technologies based on technical and financial parameters, with Eordaia, a region in energy transition and part of the RESPONSE Horizon project, illustrating the practical benefits. It includes a neighborhood of 105 mixed-use properties and two municipal buildings where a range of renewable energy sources and energy efficiency measures are applied. Insulation, photovoltaic systems, LED lighting, predictive thermostats, and windows coated with nanotechnology are some of the key interventions considered. The findings show considerable reductions in CO2 emissions and energy use, with payback periods ranging from 8.7 to 9.6 years. This study underscores the value of district-level strategies over individual building retrofits, highlighting cost savings and improved energy performance. These findings offer valuable insights for urban planners and policymakers aiming to transform urban areas into sustainable, positive energy districts, supporting the EU’s 2050 net-zero emissions goals.